2018
DOI: 10.1007/s11010-018-3428-3
|View full text |Cite
|
Sign up to set email alerts
|

HGF promotes HTR-8/SVneo cell migration through activation of MAPK/PKA signaling leading to up-regulation of WNT ligands and integrins that target β-catenin

Abstract: Inadequate migration and invasion of the trophoblast cells during embryo implantation is one of the reasons for pregnancy-related complications such as intrauterine growth restriction and preeclampsia. In the present study, relevance of WNT ligands and integrins associated with hepatocyte growth factor (HGF)-mediated migration of HTR-8/SVneo trophoblastic cells has been investigated. Treatment of HTR-8/SVneo cells with HGF led to a dose-dependent increase in their migration. RT-PCR studies revealed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…1 and 2). Significant increase in migration by HGF under normoxic conditions has been previously published by our group (Chaudhary et al 2018). The increase in migration that we observed in HGF treated HTR-8/ SVneo cells might be due to activation of c-Met protein as reported by previous studies in JEG-3 cell line and glioblastoma cell lines under hypoxic conditions (Hayashi et al 2005;Eckerich et al 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…1 and 2). Significant increase in migration by HGF under normoxic conditions has been previously published by our group (Chaudhary et al 2018). The increase in migration that we observed in HGF treated HTR-8/ SVneo cells might be due to activation of c-Met protein as reported by previous studies in JEG-3 cell line and glioblastoma cell lines under hypoxic conditions (Hayashi et al 2005;Eckerich et al 2007).…”
Section: Discussionsupporting
confidence: 86%
“…We have previously shown relevance of MAPK and PKA signaling pathways during migration of HTR-8/SVneo cells subsequent to treatment with HGF under normoxia (Chaudhary et al 2018). To investigate, which signaling pathways were activated during HGF-mediated HTR-8/SVneo cells migration/invasion under hypoxic conditions, HTR-8/ SVneo cells were serum starved and subsequently treated with and without HGF for 10, 30 and 60 min under hypoxic conditions.…”
Section: Hgf Activates Erk½ and Pi3k Signaling Pathways That Are Invomentioning
confidence: 99%
“…α1β1, α5β1, αvβ3, and αvβ5 promote trophoblast migration and invasion [17][18][19][20][21][22][23]. In addition, α5β1 enhances Fig.…”
Section: Integrinsmentioning
confidence: 97%
“…Knauf et al [29] found that HGF/Met activation mediates the resistance of mouse anaplastic thyroid cancer to BRAF inhibition, but its mechanism of action is not yet clear. In addition, both EGF and HGF can induce the activation of β-catenin and promote cell migration [30,31], thereby activating the Wnt/β-catenin signaling pathway.. The abnormal activation of Wnt /β-catenin signaling pathway is usually caused by somatic mutations, and its hot-spot mutation genes include: CTNNB1, KRAS, BRAF, NRAS, ERBB2, MET, PIK3CA, JAK1, etc [32].…”
Section: Discussionmentioning
confidence: 99%